Learning Process Experiment through Peer Tutoring in the Typography Subject from Students Learning Motivation of Arts Department FBS UNP - Yusron Wikarya; Syafei Syafei; Yofita Sandra; Ernis Ernis (Fakultas Bahasa dan Seni UNP, 2022)
The goal of this study is to see how peer tutoring strategies and student learning motivation affect Typography learning outcomes at Fine Art Department Faculty of Languages and Arts Universitas Negeri Padang (FBS UNP), as well as how they interact with one another. A quasi-experimental design with a 2X2 factorial design was used in this study. To collect research data, a learning motivation questionnaire and learning outcomes tests were used. After that, the data was analyzed using the Analysis of Variance Test (ANOVA). The research findings show that: 1) students who are taught using peer tutoring strategies have different or higher typography learning outcomes than students who are taught conventionally or without using peer tutoring strategies, 2) High learning motivation students have different or higher typography learning outcomes than low learning motivation students. According to the study's findings, peer tutoring strategies and learning motivation improve student learning outcomes in Typography courses. In terms of influencing student learning outcomes, they are not mutually dependent. As a result, peer tutoring strategies are extremely effective, and lecturers must continuously improve learning motivation throughout the learning process in order to improve student learning outcomes, particularly in the Typography subject.